Kultura myślenia Jana Pawła II (na podstawie czasopism społeczno-politycznych i społeczno-kulturalnych). Ujęcie językoznawcze = John Paul II`s culture of thinking (based on the socio-political and socio-cultural journals ). Linguistics approach - Kaczor, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Culture thinking of John Paul II is closely related to social ethics, with a broad affirmation of man and his well-being and all human values. The newspaper cites communications to the papal speech, which go deep into the realm of human spirituality, which express the spirituality and both shape and reflect concern about the ethics of speech that does not flatten or falsified picture of reality.
Keywords: Jan Paweł II, papież (1929-2005); John Paul II; kultura; culture; czasopismo społeczno-kulturalne; czasopismo społeczno-polityczne; socio-cultural magazine; socio-political magazine